Employment law - Lockton, Deborah J. (Palgrave Macmillan, 2003)
Employment law is one of the fastest moving areas in the law , with statuary changes, European decisions and new cases changing the detail very rapidly. This book steers the student through the complexities providing summary points at the end of each chapter as well as exercises and additional reading. The fourth edition has been fully updated to cover changes in the field.